2018
DOI: 10.1007/s12603-018-1008-6
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Advanced Practice Nurse in the Management of Geriatric Conditions: Examples from Different Countries

Abstract: The increasing demand for healthcare services is placing great strain on healthcare systems throughout the world. Although the older population is increasing worldwide, there is a marked deficit in the number of persons trained in geriatrics. It is now recognized that early detection and treatment of geriatric conditions (e.g., frailty, sarcopenia, falls, anorexia of aging, and cognitive decline) will delay or avert the development of disability. At the same time, recent years have seen an increased interest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 88 publications
1
17
0
2
Order By: Relevance
“…to the management of patients' health and well-being needs regardless of diagnosis. For example, older adults can be seen as a vulnerable group, and research has found that NPs caring for older adults focus on maintaining their health through health-promoting treatments, chronic disease management and the diagnosis and treatment of minor acute illnesses (85,89).…”
Section: Role and Scope Of Practice Of Nurse Practitioners Working In Primary Carementioning
confidence: 99%
“…to the management of patients' health and well-being needs regardless of diagnosis. For example, older adults can be seen as a vulnerable group, and research has found that NPs caring for older adults focus on maintaining their health through health-promoting treatments, chronic disease management and the diagnosis and treatment of minor acute illnesses (85,89).…”
Section: Role and Scope Of Practice Of Nurse Practitioners Working In Primary Carementioning
confidence: 99%
“…Several US studies adopted the quality improvement (QI) and safety approach by: a) testing programme results (Fortinsky et al 2014;Ganz et al 2010;Ouslander et al 2011;Rantz et al 2010;Reuben et al 2013) , b) comparing care by provider type -NPs vs. primary care physicians (Jennings et al 2016) and c) implementing an evidence-based quality improvement program (Donald et al 2013;Unroe et al 2015).…”
Section: Striving For Quality Improvement and Safetymentioning
confidence: 99%
“…In regard to independent functions, US APNs provided a critical link to evidence-based practice and focused on QI and patient safety (Donald et al 2013;Jennings et al 2016;Ouslander et al 2011;Reuben et al 2013;Unroe et al 2015). This finding reflected US health policy focus on improving quality, while reducing Medicare costs and enhancing primary care (Fortinsky et al 2014). Therefore, as physician substitutes, APNs in the US enhanced mutual accountability (strategy #2) and strove for an enabling environment (strategy #5) in order to provide elderly centred care.…”
Section: Apn Contributions By Role Ipchs Strategies and Approachesmentioning
confidence: 99%
“…The nurse practitioner (NP) role is being expanded globally as an innovative solution to managing the increasing healthcare demands of older adults with chronic diseases [1][2][3], a group that often has complex healthcare needs requiring provider continuity. NPs' unique advanced nursing and extended medical skills are important in caring for this group.…”
Section: Introductionmentioning
confidence: 99%